Pengaruh Promosi Media Sosial Terhadap Keputusan Pembelian Produk Kosmetik Daviena Dengan Brand Image Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa FEB Unisma) - Isnulsari, Melly; Hidayati, Nur; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine the effect of Social Media Promotion on Purchasing Decisions for Daviena Cosmetic Products through Brand Image as an intervening variable. Data was collected using purposive sampling from 95 respondents through questionnaires with a Likert Scale. Data analysis was performed using path analysis, Sobel test, and hypothesis testing (t-test) with the IBM SPSS 25 program. The results showed that partially, Social Media Promotion had a positive and significant effect on Purchasing Decisions (significance 0.000 < 0.05), Brand Image had no effect on Purchasing Decisions (significance 0.323 > 0.05), and Social Media Promotion had a positive and significant effect on Brand Image (significance 0.000 < 0.05). Meanwhile, from the Sobel test results, Brand Image was not able to mediate between the Social Media Promotion and Purchasing Decision variables (Two-tailed probability value 0.32212151 > 0.05). Keywords: Social Media Promotion, Purchasing Decisions, Brand Image, Intervening Variable